2015
DOI: 10.1007/s10620-015-3730-9
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 Level Correlates with Hepatocellular Carcinoma Cell Proliferation, Apoptosis, and EMT

Abstract: TPX2 expression is associated with proliferation, apoptosis, and EMT in hepatocellular carcinoma cell and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…For instance, TPX2 -siRNA decreased the viability and proliferation capacity of colon, cervical, and hepatic cancer cell lines [13, 14, 18]. Similarly, TPX2 -siRNA induced cell apoptosis in hepatic cancer cell lines [12]. Moreover, injection of TPX2 -siRNA significantly reduced the growth and weight of already developed xenograft tumors in nude mice [1315, 21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TPX2 -siRNA decreased the viability and proliferation capacity of colon, cervical, and hepatic cancer cell lines [13, 14, 18]. Similarly, TPX2 -siRNA induced cell apoptosis in hepatic cancer cell lines [12]. Moreover, injection of TPX2 -siRNA significantly reduced the growth and weight of already developed xenograft tumors in nude mice [1315, 21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Based on histological differences, liver cancer can be divided into three types, the most common of which is hepatocellular carcinoma (HCC), which accounts for approximately 90% of primary liver cancers [2, 3]. At present, experts believe that in China hepatitis B is one of the main pathogenic factors in HCC, and our previous work indicated that more than 90% of HCC patients are diagnosed with hepatitis B [4, 5], which can progress to liver fibrosis and cirrhosis, and may ultimately lead to tumorigenesis [6, 7]. Generally, HCC is initially asymptomatic and patients show typical symptoms only once the disease has progressed to the advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous follow-up studies showed that recurrence or metastasis within five years is observed in approximately 60% of HCC patients undergoing radical resection [4, 5]. Most researchers think this phenomenon is correlated with biological characteristics of high recurrence and the metastatic potential of HCC [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that TPX2 is overexpressed in different types of human cancers, including medullary thyroid cancer 13, esophageal squamous cell carcinoma (ESCC) 14, estrogen receptor-positive metastatic breast cancers 15 and bladder carcinoma 16, and promotes tumor growth and metastasis, including in HCC. The expression level of TPX2 was obviously higher in HCC, and TPX2 overexpression was positively correlated with poor prognosis, metastasis, recurrence and time of recurrence after curative resection 17-19. TPX2 might be beneficial for T-cell specific HCC immunotherapy 20.…”
Section: Introductionmentioning
confidence: 97%